GREEN TOURISM DALAM PENGEMBANGAN PARIWISATA BANGKA BELITUNG - Rulyanti Susi Wardhani; Devi Valeriani (Jurnal Ilmiah Ekonomi Global Masa Kini)
Tin in Bangka Belitung Province is currently no longer a commodity that can be relied upon, so that the need for other sectors that replaced the tourism sector. Tourism in Bangka Belitung Province known for the sea and its shores. When in fact the potential of forests and the environment is not less interesting if it is packed with the concept of using the environment as a tourist attraction. The research objective is to map the first year, giving a conception and model of development based on green tourism tourism management. The analytical tool used in this research is SWOT analysis, and analysis of this study found that GAP.Hasil fighting forest, hills and hills lap Menumbing proposed to the government of the District for the model-based development of green tourism. There are two alternative models offered by the first model of the concept of green tourism development with a focus on the commitment of stakeholders to establish a synergy between government, academia, entrepreneurs and media tour. The second model is the development of the first model by adding a promotion for the development of tourist attraction concept of green tourism. If the local government or attraction managers feel that the sale is still very important and the need for cooperation with community stakeholders in tourism from other areas as a comparison or input, then the second model can be applied. Keyword : GreenTourism, SWOT Analysis, Gap Analysis